Irminger Sea Is the Center of Action for Subpolar AMOC Variability - Chafik, L.; Holliday, N. P.; Bacon, S.; Rossby, T. (Geophysical Research Letters, 2022)
Significant societally important climate impacts can be caused by changes in the strength of the Atlantic Meridional Overturning Circulation (AMOC) at higher latitudes. Focusing on variability and long-term change of the subpolar North Atlantic (SPNA)—a key AMOC action center—and using eastern OSNAP array observations, we identify a distinct density and sea-surface height signature of the AMOC strength in the Irminger Sea (2014–2018), reinforced and extended with an ocean reanalysis (1993–2018). Reconstruction of AMOC variability using Irminger Sea density shows strong control by the North Atlantic Oscillation on subpolar overturning on multiple timescales, achieved via the gyre circulation and waters from the Labrador Sea. Furthermore, the observed decrease of Irminger Sea density since the mid-twentieth century (1950–2019) is suggestive of a long-term AMOC weakening of 2.2 Sv or 13%, however, this trend remains statistically insignificant due to the large interannual and decadal variability of the SPNA.